Pengaruh Kombinasi Jus Tomat dan Massage Kaki Rendam Air Hangat terhadap Tekanan Darah Penderita Hipertensi - Mulyani, Sri; Yudiatma, Muh Firman; Putrian, Resa (JURNAL WACANA KESEHATAN, 2025)
Hypertension is a non-communicable disease that often leads to severe complications such as stroke and heart failure. Non-pharmacological therapy is an essential alternative to control blood pressure without drug side effects. This study aimed to determine the effect of a combination of tomato juice and warm foot massage therapy on blood pressure among hypertensive patients in WR Jengkol Village. This research employed a Quasi-Experimental design with a Pre-test and Post-test Control Group Design and purposive sampling involving 34 respondents divided into intervention and control groups. The Paired T-Test results showed a significant reduction in systolic and diastolic blood pressure in the intervention group (p-value 0.000 < 0.05), with a mean decrease of 30.59 mmHg for systolic and 15.88 mmHg for diastolic pressure, while the control group showed no significant changes. The combination of tomato juice and warm foot massage effectively lowered blood pressure through biochemical effects (lycopene, potassium, antioxidants) and physiological mechanisms (peripheral vasodilation and muscle relaxation). This therapy is recommended as a safe, simple, and cost-effective non-pharmacological approach for hypertension management.